2014
DOI: 10.1002/jctb.4389
|View full text |Cite
|
Sign up to set email alerts
|

Application of bioassay panel for assessing the impact of advanced oxidation processes on the treatment of reverse osmosis brine

Abstract: BACKGROUND: The persistence of microcontaminants through conventional wastewater treatments is a matter of concern and it suggests the implementation of advanced treatment steps. Although there is evidence that reverse osmosis (RO) is the most efficient treatment for the the removal of these compounds, it has the drawback of producing significant amounts of highly polluted brine. In this work, chemical analyses and toxicity bioassays were combined to evaluate the removal of different pharmaceuticals and of dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In general, incomplete oxidation can generate species that can be more toxic than parent molecule. In order to assess treated water, chemical analysis and bioassays are suggested [72][73][74]. If the raw feed water is too heavily laden with natural organic matter, then pretreatment such as microfiltration may also be necessary.…”
Section: Hydrogen Peroxide Ozone Model Resultsmentioning
confidence: 99%
“…In general, incomplete oxidation can generate species that can be more toxic than parent molecule. In order to assess treated water, chemical analysis and bioassays are suggested [72][73][74]. If the raw feed water is too heavily laden with natural organic matter, then pretreatment such as microfiltration may also be necessary.…”
Section: Hydrogen Peroxide Ozone Model Resultsmentioning
confidence: 99%
“…Our results can be compared with comparable assays that used βNF as the positive control to estimate BEQs. Yeast cells transfected with human AhR and its dimerization partner, the human aryl hydrocarbon receptor nuclear translocator (ARNT), have found BEQ values for river water ranging from ∼10 to 950 ng/L BEQ, , 390 to 740 ng/L in wastewater treatment plant effluent, and 2 000 ng/L to 1 500 μg/L in untreated wastewater. In one of the studies measuring BEQ of river water, the sites with the highest BEQ values (200–950 ng/L) were located within an industrial textile region of Japan, an area known for containing AhR agonists due to contributions from dye industry effluents . The second study examining BEQ values in river water similarly found the highest BEQ values (approximately 50–130 ng/L) to be located within an industrialized region .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AhR-mediated pathways does not always lead to adverse health outcomes. However, it has been demonstrated that activation of these pathways over a period of time and over a threshold amount leads to adverse health outcomes in vertebrates . Risk is proportional to activation of the AhR pathways, when that activation occurs over a threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Physico-chemical methods include photodegradation [9], oxidation [10,11], absorption on active carbon [12,13] and classical membrane processes such as ultrafiltration and nanofiltration [14,15].…”
Section: Introductionmentioning
confidence: 99%